Die Mär vom Kalten Krieg. Wie geopolitische Paradigmen in den Internationalen Beziehungen des Arktisraums (re)produziert werden - Knecht, Sebastian (Sicherheit & Frieden, 2015)
Knecht S. Die Mär vom Kalten Krieg. Wie geopolitische Paradigmen in den Internationalen Beziehungen des Arktisraums (re)produziert werden. S+F Sicherheit und Frieden . 2015;33(3):121-126. The Arctic region has gained momentum in international relations following a record low of sea ice in 2007 and associated economic prospects. Since then, political, public and academic discourses alike have perceived the Arctic as a potential arena for peace and conflict studies. Despite the low cogency of many Arctic geopolitical analyses predicting regional conflict, three recent developments have reinforced the image of a contested Arctic: increased interest from Asian actors; strained diplomatic relations between Russia and its Western partners over the 2014 Ukraine crisis; and, related to this, the re-militarization of the Russian North. As will be argued here, this ’new Arctic geopolitics’ is about to repeat the same fallacies and analytical traps than previous scenarios.